THE RELATIONSHIP BETWEEN MALNUTRITION AND SEVERE PNEUMONIA AMONG TODDLERS IN EAST JAVA, INDONESIA : AN ECOLOGICAL STUDY - Prastika, Milistia Kristi; Astutik, Erni (Journal of Public Health Research and Community Health Development, 2023)
ABSTRACT Background: The case of toddler mortality in the world due to pneumonia is still relatively high. In community-acquired-pneumonia, severity was an independent risk factor for death. Malnutrition and infectious diseases have a mutually influential relationship with each other. The high cases of pneumonia and malnutrition in toddlers in East Java Province need to be considered because they will support the welfare of the 3rd Sustainable Development Goal, in this case, it is necessary to conduct research on nutrition and pneumonia in toddlers in East Java Province Purpose: To analyze the relationship between malnutrition and severe pneumonia in toddlers in East Java Province in 2019-2020 Methods: This research design used an ecological study with district/city in the East Java Province as the analysis unit. The data were taken from the health profile of East Java Province. The data analysis technique used was the Spearman test. Results: The study showed that there was a relationship between malnutrition and pneumonia in toddlers because p = 0.001 < = 0.05. Conclusion: There is a strong relationship between cases of severe pneumonia and malnutrition in toddlers in the East Java Province in 2019-2020 with a positive relationship direction.